Systematic review and meta-analysis: SGLT2 inhibitors, blood pressure and cardiovascular outcomes. (April 2021) - Benham, Jamie L.; Booth, Jane E.; Sigal, Ronald J.; Daskalopoulou, Stella S.; Leung, Alexander A.; Rabi, Doreen M.
Abstract: Objective: Clinical trials suggest that SGLT2 inhibitors reduce the risk of cardiovascular mortality in patients with type 2 diabetes, however the mechanism is unclear. Our objective was to test the hypothesis that blood pressure reduction is one potential mechanism underlying the observed improvements in cardiovascular outcomes with SGLT2 inhibitors. Methods: We searched MEDLINE, EMBASE and Cochrane Central Register of Controlled Trials (inception-June 2019) for randomized controlled trials that reported the effect of SGLT2 inhibitors compared with placebo on cardiovascular outcomes in adults with type 2 diabetes. Two reviewers independently extracted data and assessed study quality. Random effects meta-analyses, stratified meta-analyses and meta-regressions were conducted to evaluate the association between blood pressure reduction in SGLT2 inhibitor treated patients and cardiovascular outcomes. Results: Of 11, 232 articles identified, 40 articles (n = 54, 279 participants) were included. The relative risk of cardiovascular mortality was reduced by 18% with the use of SGLT2 inhibitors compared with placebo (RR 0.82; 95%CI 0.74, 0.91, I 2  = 0.0%). Meta-regression analysis revealed no detectable difference in cardiovascular mortality (RR 0.93; 95%CI 0.88, 1.13, p = 0.483), 3-point major adverse cardiovascular events (p = 0.839) or congestive heart failure hospitalizations (p = 0.844) with change in mean systolic blood pressure. Conclusions: Cardiovascular events are reduced in participants with type 2 diabetes treated with SGLT2 inhibitors compared with placebo. There was no significant relationship between the risk of developing adverse cardiovascular events and blood pressure reduction with SGLT2 inhibitors. There is insufficient evidence to suggest that blood pressure reduction is a significant contributor to the cardiovascular benefits observed.